2017
DOI: 10.1016/j.bbamem.2017.01.001
|View full text |Cite
|
Sign up to set email alerts
|

The random co-polymer glatiramer acetate rapidly kills primary human leukocytes through sialic-acid-dependent cell membrane damage

Abstract: The formulation glatiramer acetate (GA) is widely used in therapy of multiple sclerosis. GA consists of random copolymers of four amino acids, in ratios that produce a predominantly positive charge and an amphipathic character. With the extraordinary complexity of the drug, several pharmacological modes-of-action were suggested, but so far none, which rationalizes the cationicity and amphipathicity as part of the mode-of-action. Here, we report that GA rapidly kills primary human T lymphocytes and, less active… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 56 publications
1
20
0
Order By: Relevance
“…The zeta potential was still below −10 mV at pH 7.4 and below −19 mV at pH 8.0 even at the 4.5th h. Similar phenomenon was also reported in many literatures. [12,16b,25] These results clearly demonstrated the appreciable acidity‐triggered charge reversible ability of C 16 –PRP–DMA nanoparticles. The different zeta potential values of C 16 –PRP–DMA at 1 min at different pHs were due to the different ionization state of the guanidine groups in the side chain of RRKK sequence.…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…The zeta potential was still below −10 mV at pH 7.4 and below −19 mV at pH 8.0 even at the 4.5th h. Similar phenomenon was also reported in many literatures. [12,16b,25] These results clearly demonstrated the appreciable acidity‐triggered charge reversible ability of C 16 –PRP–DMA nanoparticles. The different zeta potential values of C 16 –PRP–DMA at 1 min at different pHs were due to the different ionization state of the guanidine groups in the side chain of RRKK sequence.…”
Section: Resultsmentioning
confidence: 76%
“…What's more, many membrane proteins (such as ATP‐binding cassette transporter), and the reversal of the pH gradient at plasma membrane (∆pHcm), might promote resistance of cancer cells to many chemotherapy drugs . Considering the unique feature of cell membrane, direct destruction of tumor cell membrane would be a novel and efficient approach for tumor inhibition . Comparing with the conventional antitumor strategy, cell membrane‐targeted therapy can be more efficient since it could take effect without the cell endocytosis of drugs.…”
Section: Introductionmentioning
confidence: 99%
“…We recently demonstrated that NTA measurement enables a high sensitivity in measuring damage to cell membranes 25 . Moreover, this technique also measures the size of particles into the nm-regimen, enabling ultrastructural characterization of AMP-induced fragmentation of bacteria.…”
Section: Resultsmentioning
confidence: 99%
“…GA copolymers are made from random copolymerization of the acetic anhydrides of l -glutamate, l -lysine, l -alanine, and l- tyrosine in molar ratios that produce polymers with an overall cationic and amphipathic character 24 . It was recently demonstrated that the chemical and biophysical properties of GA are similar to LL-37 25 , including the ability of GA to disrupt lipid bilayers. GA’s composition of random copolymers is reminiscent of temporins and dermaseptins.…”
Section: Introductionmentioning
confidence: 99%
“…More recent studies suggest that GA may also directly kill certain T cells, apparently depending on the expression of sialic acid decoration of proteins in the target cell membrane. This effect seems to be shared with human endogenous peptide, LL‐37, usually referred to as an antimicrobial peptide, but a substance with considerable directs effects also on human leucocytes .…”
Section: Potentials Of Glatiramer Acetate Therapy In Parkinson's Disementioning
confidence: 95%